Proinflammatory Cytokines Increase Vascular Endothelial Growth Factor Expression in Alveolar Epithelial Cells - James P. Maloney; Li Gao (Hindawi Limited, 2015)
Vascular endothelial growth factor (VEGF) is an endothelial permeability mediator that is highly expressed in lung epithelium. In nonlung cells proinflammatory cytokines have been shown to increase VEGF expression, but their effects on lung epithelium remain unclear. We hypothesized that increases in alveolar epithelial cell VEGF RNA and protein expression occur after exposure to proinflammatory cytokines. We tested this using human alveolar epithelial cells (A549) stimulated with 5 proinflammatory cytokines. VEGF RNA expression was increased 1.4-2.7-fold in response to IL-1, IL-6, IL-8, TNF-α, or TGF-β over 6 hours, with TGF-β having the largest response. TNF-α increased VEGF RNA as early as 1 hour. A mix of IL-1, IL-6, and IL-8 had effects similar to IL-1. TNF-α increased protein expression as early as 4 hours and had a sustained effect at 16 hours, whereas IL-1 did not increase protein expression. Only VEGF165 was present in cultured A549 cells, yet other isoforms were seen in human lung tissue. Increased expression of VEGF in alveolar epithelial cells occurs in response to proinflammatory cytokines. Increased VEGF expression likely contributes to the pathogenesis of inflammatory lung diseases and to the angiogenic phenotype of lung cancer, a disease typically preceded by chronic inflammation.